1978
DOI: 10.1128/aac.13.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Nephrotoxicity of Gentamicin and Tobramycin in Rats

Abstract: A rat model was utilized to compare the nephrotoxic potential of gentamicin and tobramycin. Gentamicin, 40 mg/kg per day, predictably produced renal failure and morphological evidence of proximal tubular necrosis over 14 days of treatment. An identical dosage of tobramycin was associated with only minimal morphological changes and normal concentrations of serum creatinine and blood urea nitrogen. Similar results were obtained even after the tobramycin dosage was tripled to 120 mg/kg per day. A decrease in urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1
3

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 26 publications
5
25
1
3
Order By: Relevance
“…Although our data do not establish a significant difference between gentamicin and tobramycin with respect to the risk of nephrotoxicity, several recent studies have shown that tobramycin has significantly lower nephrotoxic potential in experimental animals (13,31). This difference may be partially accounted for by the greater concentration of gentamicin in the renal cortex (27).…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…Although our data do not establish a significant difference between gentamicin and tobramycin with respect to the risk of nephrotoxicity, several recent studies have shown that tobramycin has significantly lower nephrotoxic potential in experimental animals (13,31). This difference may be partially accounted for by the greater concentration of gentamicin in the renal cortex (27).…”
Section: Resultscontrasting
confidence: 83%
“…For the most part, the azotemia associated with AMG therapy is reversible upon discontinuation of the antibiotic. Histological examination reveals primarily proximal tubular necrosis, manifested clinically by rising blood urea nitrogen and creatinine and decreased ability to concentrate urine (5,13). Risk factors for development of nephrotoxicity are not fully agreed upon.…”
Section: Resultsmentioning
confidence: 99%
“…The lesions observed were identical to those previously described in similar aminoglycoside nephrotoxicity studies in rats (8,10,11,16). The lesions observed in F344 rats were similar to those observed in Sprague-Dawley rats but were quantitatively more pronounced.…”
Section: Pathologysupporting
confidence: 86%
“…Tobramycin is an aminoglycoside derivative that has potent renal toxicity (18), and this toxicity is potentiated in combination with vancomycin (19). It has been shown recently that tobra mycin inhibits Na,Ca-ATPase and accelerates urinary cal cium excretion (20).…”
Section: Discussionmentioning
confidence: 99%